Evolution and development of drug therapy for triple negative breast neoplasms: an integrative review (Research, Society and Development, 2023)
This article aims to analyze and criticize the existing experiences of pharmacological therapy for the treatment of triple-negative breast cancer (TNBC), in order to understand the possibility of significant advances in the area. TNBC, in particular, generates an intense concern among health professionals, patients, and families due to the high frequency of unfavorable prognosis and its incidence in young patients. Thus, it was decided to carry out the integrative literature review model, using as a bibliographic framework the articles in the electronic databases: PUBMED (Publisher Medline) and VHL (Virtual Health Library). Therefore, those publications that correctly related the keywords and passed through the selection filters were chosen, that is, those that contained relevant information and were capable of substantially adding to the discussion. Then, data was collected about the performance of different drugs in the treatment of 6 different types of TNBC, including cyclophosphamide, taxanes, and platinum, among others. In addition, positive results were also found for the combination of different drugs, and the alliance with more traditional methods such as chemotherapy, establishing neoadjuvant chemotherapy. In addition to the improvement in survival rates resulting from experiments carried out with checkpoint inhibitor drugs and even the approval of some of these by federal health bodies, it is possible to infer that the existing pharmacological treatments denote an adequate result, but which represents, however, a minority portion of the great potential to be explored through the development of new therapeutic procedures with drugs already known to be effective, and with new ones that have yet to be tested.